PENGARUH DISIPLIN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KUALITAS KERJA DAN KINERJA KARYAWAN PT BPD KALTIM KALTARA CABANG BONTANG - SAYID MOHAMMAD HANAFIAH; Prof. Dr. Sukisno S. Riadi; Dr. Doddy Adhimursandi, SE, MM (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
This research is a causality research using primary data and secondary data, while the object of research is employees of BPD Kaltim Kaltara Bontang Branch with the number of samples of 47 respondents. The purpose of this study is to analyze and prove the influence of work discipline on the quality of work employees. Analyze and prove the influence Organizational commitment to the quality of work of employees. Analyze and prove the influence of work discipline on employee performance. Analyze and prove the influence of Organizational Commitment on employee performance. Analyze and prove the effect of work quality on employee performance.In order to test the hypothesis analysis the author uses the Structural Equation Modeling analysis tool with SmartPLS. Respondents of this study were employees of PT BPD Kaltim Kaltara Branch Bontang with a total sample of 47 respondents. The results of the analysis show that work discipline has no significant effect on the quality of work of PT BPD Kaltim Kaltara employees in Bontang Branch. Organizational commitment has a significant effect on the quality of work of employees of PT BPD Kaltim Kaltara, Bontang Branch. Work discipline has no significant effect on the performance of employees of PT BPD Kaltim Kaltara, Bontang Branch. Organizational commitment has a significant effect on the performance of employees of PT BPD Kaltim Kaltara, Bontang Branch. The quality of work has a significant effect on the performance of employees of PT BPD Kaltim Kaltara Branch Bontang.